2012
DOI: 10.1039/c2cp23258h
|View full text |Cite
|
Sign up to set email alerts
|

Fully Λ-doublet resolved state-to-state differential cross-sections for the inelastic scattering of NO(X) with Ar

Abstract: Fully Λ-doublet resolved state-to-state differential cross-sections (DCSs) for the collisions of the open-shell NO(X, (2)Π(1/2), ν = 0, j = 0.5) molecule with Ar at a collision energy of 530 cm(-1) are presented. Initial state selection of NO(X, (2)Π(1/2), j = 0.5, f) was performed using a hexapole so that the (low field seeking) parity of ε = -1, corresponding to the f component of the Λ-doublet, could be selected uniquely. Although the Λ-doublet levels lie very close in energy to one another and differ only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
93
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(100 citation statements)
references
References 44 publications
6
93
0
1
Order By: Relevance
“…[16][17][18][19][20] Recently, the inelastic scattering dynamics of methyl radical with He, 21 H2 and D2, 22 and Ar 23 were examined using crossed molecular beam methods in combination with velocity map imaging (VMI …”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] Recently, the inelastic scattering dynamics of methyl radical with He, 21 H2 and D2, 22 and Ar 23 were examined using crossed molecular beam methods in combination with velocity map imaging (VMI …”
Section: Introductionmentioning
confidence: 99%
“…Accurate potential energy surfaces have been constructed 8,9 on which extensive scattering calculations have been performed. The primary focus of many of these studies has been on the integral 8 and differential [10][11][12][13] cross sections, particularly more recently on explaining parity dependent structure in the integral 8 and differential [11][12][13] cross sections. The integral cross sections show periodic alternations in magnitude as a function of j and of the NO(X) parity changing/conserving nature of the transition.…”
Section: Introductionmentioning
confidence: 99%
“…11-13 -doublet resolved DCSs have been measured recently using velocity map ion-imaging, and have been shown to be in excellent agreement with quantum mechanical (QM) scattering theory. [11][12][13] Relatively fewer investigations have been directed towards polarization effects in this collision system. The collision-induced alignment of NO(X), averaged over the unselected initial -doublet level, was first measured experimentally by Cline et al 14 and Wade et al 15 For the low j states they found reasonable agreement between the experiment and the close-coupled quantum mechanical (CC QM) scattering theory results obtained using the CCSD(T) PESs of Alexander.…”
Section: Introductionmentioning
confidence: 99%
“…The IMSIM and Monte Carlo methods for generating these instrument functions have been described in detail elsewhere. [43][44][45][46][47][48] Here, we focus on the determination of key parameters that are input to these codes to account for the conditions specific to our experimental set up.…”
mentioning
confidence: 99%